Water slurry gasification coal gas waste heat recovery utilizes system - PEI PEI; WU DAOHONG; SUN BAOLIN (2016)
The utility model provides a water slurry gasification coal gas waste heat recovery utilizes system. The utility model discloses a water slurry gasification coal gas waste heat recovery utilizes system includes: water slurry gasification stove (3), fluidized bed gasifica tion device (4), gaseous heat exchanger (5) and fluidized bed pyrolyzer (6), the coal gas of water slurry gasification stove (3) export with the gas feed of fluidized bed gasifica tion device (4) connects, the gas outlet of fluidized bed gasifica tion device (4) with the gas inlet of gaseous heat exchanger (5) connects, the nitrogen gas export of gaseous heat exchanger (5) with the gas feed of fluidized bed pyrolyzer (6) connects. The utility model provides a because fluidized bed gasifica tion's coal gas waste heat recovery utilizes and the system of purification, combined fluidized bed gasifica tion's technological advantages, whole system device is simple, easily operation, thermal efficiency height, it is pollution -free. 本实用新型提供了种水煤浆气化煤气